PELAKSANAAN TUGAS DAN FUNGSI BADAN NARKOTIKA NASIONAL KOTA PEKANBARU DALAM PENCEGAHAHAN PENYALAHGUNAAN NARKOTIKA DI KOTA PEKANBARU TAHUN 2018 - Yono, Andri; M, Erman (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2020)
The current condition of drug abuse in Indonesia is a very worrying problem, Indonesia is in a state of emergency on drugs. Drugs have spread throughout districts and cities in 33 provinces. This means that no area is free from drug trafficking. Geographically, Riau is close to neighboring countries such as Malaysia and Singapore, so it has a high potential for conflict. Its strategic location makes Riau an entry point for radicalism and drug trafficking. This situation has resulted in Riau, especially Pekanbaru City, becoming an area that is vulnerable to the infiltration of drug trafficking in the community. This study aims to describe the implementation of the duties and functions of the Pekanbaru City National Narcotics Agency in the Prevention of Narcotics Abuse in Pekanbaru City in 2018. In addition, to determine the inhibiting factors for this implementation. This research uses descriptive qualitative methods and data collection techniques based on observation, literature study and interviews. The results of this study can be seen that the implementation of the duties and functions of the Pekanbaru City National Narcotics Agency in Preventing Narcotics Abuse in Pekanbaru City in 2018 is quite good, but there are several problems such as ineffective implementation of the duties and functions of the City National Narcotics Agency, the establishment of anti-drug-oriented development policies by the Pekanbaru City BNN. in the field of prevention. As for the inhibiting factors, namely the lack of BNN Pekanbaru City budget in carrying out its duties and functions, the lack of facilities and infrastructure for BNN Pekanbaru City and the lack of support from the leadership of SKPD (Regional Government Performance Units) in Pekanbaru City in implementing the P4GN program. Keywords: Duties and Functions, National Narcotics Agency (BNN), Prevention, Abuse, Narcotics.